Plug in battery electric vehicle - fabrication of vehicle chassis and conceptual deisgn of dashbar - Zhuo, Ying Jie (2015)
Global warming and pollution are perhaps the greatest threat to Earth. The burning of petrol in vehicles deeply contributes to this threat and has been causing permanent damage to both human health and the environment. In addition, the ever-growing demands for energy and reliance on depleting fossil fuel request the needs for environmentally-friendly and sustainable energy alternatives. At present, various technologies such as fuel-efficient vehicles and cleaner fuels address these issues. Among these technologies, the one that stood out is the invention of electric cars and trucks. Statistics prove that their service life is much longer; maintenance frequency is much lesser and produces little to no emission (if renewable energy is consumed to produce electricity) compare to that of petrol vehicles. Nanyang Technological University (NTU) aims to contribute to the research and development of electric cars and hence develop its own Battery Electric Vehicle (BEV). With this, NTU offers a solution for urban area to reduce the dependence of transport on oil. The author’s role in the project involved the designing of dashbar of BEV, planning and minimising beam wastage, coordinate operation for fabricating and integrating various parts of the BEV’s chassis, generating of welding steps and researches of the welding requirement to weld TIG AISI4130 Steel.